Study of Groundwater Physical Characteristics: A Case Study at District of Pekan, Pahang - Hashim M.M.M.; Zawawi M.H.; Samuding K.; Dominic J.A.; Zulkurnain M.H.; Mohamad K. (Institute of Physics Publishing, 2023)
Coastal zones; Electric conductivity of solids; Groundwater; Location; Coastal area; Coastal line; Electrical conductivity; In-situ measurement; Physical characteristics; Sampling location; Total dissolved solids; Tubewells; Tubes (components)